2014
DOI: 10.1002/chem.201403660
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Donor–π‐Acceptor‐Based Porphyrin Sensitizers: Potential Application of Dye‐Sensitized Solar Cells

Abstract: New porphyrin sensitizers based on donor-π-acceptor (D-π-A) approach have been designed, synthesized, characterized by various spectroscopic techniques and their photovoltaic properties explored. N,N'-Diphenylamine acts as donor, the porphyrin is the π-spacer, and either carboxylic acid or cyanoacryclic acid acts as acceptor. All compounds were characterized by using (1)H NMR spectroscopy, ESI-MS, UV-visible emission spectroscopies as well as electrochemical methods. The presence of aromatic groups between por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…27,30,31 However, previous work has shown that thiophene, rather than furan, when incorporated as π-bridges of porphyrin dyes results in better PCEs, presumably due to the more electron withdrawing character and/or improved interactions between the dye and TiO 2 due to thiophene moiety. [32][33][34][35] Results and discussion…”
Section: Introductionmentioning
confidence: 99%
“…27,30,31 However, previous work has shown that thiophene, rather than furan, when incorporated as π-bridges of porphyrin dyes results in better PCEs, presumably due to the more electron withdrawing character and/or improved interactions between the dye and TiO 2 due to thiophene moiety. [32][33][34][35] Results and discussion…”
Section: Introductionmentioning
confidence: 99%
“…To deeply understand our experimental results, the energies and spatial structures of LYD ‐dyes’ molecular orbitals were computerized by the hybrid DFT method on the level of B3LYP/6‐31G(d)/LANL2DZ . The electron distributions of HOMO‐1, HOMO, LUMO and LUMO+1 for these Zn‐porphyrin dyes are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The conduction band of TiO 2 is located between LUMOs and HOMOs of dyes to ensure the effective electron injection. Although two carboxyl groups of LYD‐4 show same electron distributions, one of them displays large dihedral angle (57.7°, Figure ) to the conjugated π‐plane and should be free of binding to TiO 2 surface, which would carries photoelectrons back to electrolyte leading to the lowest J sc . In contrast, both carboxylic and hydroxyl groups of LYD‐2 and LYD‐5 can transfer electrons resulting in the obvious enhancement of photovoltaic conversion efficiency of devices.…”
Section: Resultsmentioning
confidence: 99%
“…After the first report by Wang etc ., a variety of thiophene conjugated rigid acceptors have been created (Sreenivasu et al, 2014 ; Zhang M.-D. et al, 2014 ). Interesting to note that furan and bithiophene linked acceptor functionated porphyrins exhibit broader absorption area than that of thiophene but dramatically dropped performance (2.8 and 1.4%).…”
Section: The Development Of Porphyrins For Solar Cell Applicationmentioning
confidence: 99%